Post-transplant lymphoproliferative disease after pediatric kidney transplant - Fulchiero, Rosanna; Amaral, Sandra (Frontiers in Pediatrics, 2022)
Post-transplant lymphoproliferative disease (PTLD) is the most common malignancy complicating solid organ transplantation (SOT) in adults and children. PTLD encompasses a spectrum of histopathologic features and organ involvement, ranging from benign lymphoproliferation and infectious-mononucleosis like presentation to invasive neoplastic processes such as classical Hodgkin lymphoma. The predominant risk factors for PTLD are Epstein-Barr virus (EBV) serostatus at the time of transplant and the intensity of immunosuppression following transplantation; with EBV-negative recipients of EBV-positive donor organs at the highest risk. In children, PTLD commonly presents in the first two years after transplant, with 80% of cases in the first year, and over 90% of cases associated with EBV-positive B-cell proliferation. Though pediatric kidney transplant recipients are at lower risk (1-3%) for PTLD compared to their other SOT counterparts, there is still a significant risk of morbidity, allograft failure, and an estimated 5-year mortality rate of up to 50%. In spite of this, there is no consensus for monitoring of at-risk patients or optimal management strategies for pediatric patients with PTLD. Here we review pathogenesis and risk factors for the development of PTLD, with current practices for prevention, diagnosis, and management of PTLD in pediatric kidney transplant recipients. We also highlight emerging concepts, current research gaps and potential future developments to improve clinical outcomes and longevity in these patients.